Jenis Serangga Hama Pada Tanaman Cengkeh (Syzygium aromaticum) di Desa Salumpaga Kecamatan Tolitoli Utara Kabupaten Tolitoli - Sukmawati Sukmawati; Manap Trianto; Nuraini Nuraini (Unversitas Muhammadiyah Mataram, 2019)
Cloves (Syzygium aromaticum) are native to Indonesia which have high social and economic value, however cloves also have different types of pests. The latest information on insect pests in cloves is still very limited. This study aims to describe the types of insect pests found in clove (Syzygium aromaticum). This type of research is a descriptive exploratory research. Pest insect samples were taken at 3 observation locations, namely at a slope of 0%, a slope of <15% and a slope of> 15% and identification of the pests found. The results showed that at a 0% slope, the insect pests found were Coptotermes gestroi and Coptocercus biguttatus. At a slope of <15%, the insect pests found were Coptotermes gestroi, Hexamitodera semivelutina and Coptocercus biguttatus. Whereas at a slope of> 15%, the insect pests found were Coptotermes gestroi, Hexamitodera semivelutina, Coptocercus biguttatus and Nothopeus sp.